2011
DOI: 10.1002/oa.1127
|View full text |Cite
|
Sign up to set email alerts
|

Possible cases of scalping from pre‐hispanic highland Peru

Abstract: For years, the pre-Hispanic Chachapoya of Northern Peru have been described as the 'Warriors of the Clouds'.A more detailed look at newly excavated osteological samples from the highland site of Kuelap allows us to better examine the types of traumatic injuries among the Chachapoya. This paper describes an individual with evidence of a recent scalp removal including cut marks encircling the vault and a large area of active inflammatory response due to exposure of the outer table. The degree of osseous response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…Two previously reported individuals from Kuelap (Toyne, 2011b) likely represent scalping, since clear cut marks are associated with the periphery of the affected area. They are included in this study to highlight the variations in lesions and bone response observed.…”
Section: Scalp Removalmentioning
confidence: 96%
See 3 more Smart Citations
“…Two previously reported individuals from Kuelap (Toyne, 2011b) likely represent scalping, since clear cut marks are associated with the periphery of the affected area. They are included in this study to highlight the variations in lesions and bone response observed.…”
Section: Scalp Removalmentioning
confidence: 96%
“…However, while scalping has been associated with historic warfare and violence as a means of 'counting' coup or taking trophies, there have been accidental cases (Ortner, 2003;Preis et al, 2007), or other less violent reasons for removing a portion of the scalp that may have had a surgical or therapeutic purpose (Toyne, 2011b). With the overlying scalp removed, the periosteum may be damaged and lead to necrosis of the underlying normal skull tissue (without this protection and vascular supply).…”
Section: Scalp Removalmentioning
confidence: 98%
See 2 more Smart Citations
“…6). While no stone tool drills were recovered from Kuelap, several obsidian blades have been (Narváez Vargas, 2009;Toyne, 2011b). There is also evidence of two short, parallel perimortem cut marks located on the medial malleolus just inferior to the drilled aperture (Detail in Fig.…”
Section: Description Of Modified Areamentioning
confidence: 92%